Electrokinetic Analysis of Energy Harvest from Natural Salt Gradients in Nanochannels. Issue 1 (December 2017) - He, Yuhui; Huang, Zhuo; Chen, Bowei; Tsutsui, Makusu; Shui Miao, Xiang; Taniguchi, Masateru
Abstract The Gibbs free energy released during the mixing of river and sea water has been illustrated as a promising source of clean and renewable energy. Reverse electrodialysis (RED) is one major strategy to gain electrical power from this natural salinity, and recently by utilizing nanochannels a novel mode of this approach has shown improved power density and energy converting efficiency. In this work, we carry out an electrokinetic analysis of the work extracted from RED in the nanochannels. First, we outline the exclusion potential effect induced by the inhomogeneous distribution of extra-counterions along the channel axis. This effect is unique in nanochannel RED and how to optimize it for energy harvesting is the central topic of this work. We then discuss two important indexes of performance, which are the output power density and the energy converting efficiency, and their dependence on the nanochannel parameters such as channel material and geometry. In order to yield maximized output electrical power, we propose a device design by stepwise usage of the saline bias, and the lengths of the nanochannels are optimized to achieve the best trade-off between the input thermal power and the energy converting efficiency.